Exploring Chinese preschool teachers with a history of childhood abuse and neglect: impacts on emotion regulation and the role of resilience and student—teacher relationships - Tang, Yanmei; Gan, Zilu; Zhu, Jiahui (Frontiers in Education, 2025)
This study aims to examine Chinese preschool teachers who have experienced childhood abuse in regard to their emotion regulation, as well as the chain mediating effects of resilience and current student-teacher relationships. A total of 528 Chinese female preschool teachers in Jiangsu province completed the Childhood Trauma Questionnaire, Emotion Regulation Scale, Connor-Davidson Resilience Scale, and the Student-Teacher Relationships Scale. The results show that experiencing childhood abuse and neglect positively influences expression suppression and negatively affects cognitive reappraisal of preschool teachers. Results also reveal that resilience and student-teacher relationships play a chain mediation between childhood abuse and neglect and cognitive reappraisal. This study recommends that local governments, communities and educational agencies should focus on the negative impact of childhood abuse and neglect, intervening the positive influences of resilience and healthy student-teacher relationships to improve preschool teachers’ emotion regulation ability and well-being.